Subxiphoid window drainage of pericardial effusion - study of 35 cases (University Heart Journal, 2010)
Pericardial effusion defines the presence of an abnormal amount and/or character of fluid in the pericardial space. It can be acute or chronic and caused by a variety of local and systemic disorders, or it may be idiopathic. Pericardial effusion can be relieved by medical treatment, pericardiocentesis through a needle with or without echocardiographic guidance, or by surgical procedures, such as subxiphoid pericardial tube drainage, by creating a pericardial window through a left anterior thoracotomy, or by video assisted thoracoscopic surgery (VATS) Subxiphoid pericardial window drainages were done on 35 patients with symptomatic pericardial effusion in the Department of cardiac surgery, BSMMU, from February, 1995 through July, 2009, and were all included in this retrospective observational study. The inclusion criteria were an established diagnosis of pericardial effusion confirmed by history, physical findings and transthoracic echocardiography, hemodynamic alteration as evidenced by hypotension( systolic blood pressure < 90 mm of Hg), shortness of breath, echocardiographic finding of > 10 mm echo free space with/ without compression of heart, recurrence after pericardiocentesis, haemorrhagic or thick pericardial effusion and malignant pericardial effusion. The exclusion criteria were loculated or post surgical pericardial effusion, effusive constrictive pericarditis or where formal thoracotomy was applied for drainage of effusion. Patients were followed up at one month and three months following the drainage procedure. The age range was from 13 years to 70 years (Mean 47.86 ± SD 15.20 years), 19 (54.28%) were male, 16(45.72%) were female. The symptomatology varied but cardiac and respiratory decompression overwhelmed other symptoms. In this study tuberculosis is the most common cause of pericardial effusion, idiopathic and malignancies are other important causes. Subxiphoid window drainage is an effective process in relieving pericardial effusion and the reaccumulation rate is low. Key words: Subxiphoid window drainage; Surgical drainage of pericardial effusion; Pericardial effusion. DOI: 10.3329/uhj.v5i2.4558 University Heart Journal Vol.5(2) July 2009 pp.71-74